Atravessamentos e transversalizações na vida de moradores de rua : reflexões a partir de um lugar institucional no município de Aracaju-SE - Gama Júnior, César Gomes (2019)
In our daily lives, we pass by people we do not realize, sometimes blinded by the speed and daily rush. Other times, because of the difficulty in conceiving and accepting differences, we see them through the inappropriate prism of a model of life that is continually produced, uninterrupted and established as predominant. These people who make the streets and their housing and livelihood possibilities move away from this ideal, productive, bourgeois model of life and end up composing a kind of urban landscape in modern and capitalist contemporary times. It is these people, who lives on the streets, who deconstruct and reconstruct public policies, ways of living and thinking with their life stories and peculiarities that the analyzes linked here will describe and seek to expose the crossings and transversalizations in their lives.